Morphometric Study of the Human Pituitary Gland - Rahman, Mushfika; Ara, Shamim; Afroz, Halima; Nahar, Nurun; Sultana, Anjuman Ara; Fatema, Kaniz (Bangladesh Journal of Anatomy, 2013)
DOI: http://dx.doi.org/10.3329/bja.v9i2.15276 Bangladesh Journal of Anatomy 2011 Vol.9(2) pp.79-83